BIOFABRICATION OF ZINC OXIDE NANOPARTICLES USING PTEROCARPUS MARSUPIUM AND ITS BIOMEDICAL APPLICATIONS - Rajan Abhinaya, Shymala; Padmini, Ramakrishnan (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study is to perform the synthesis of zinc oxide nanoparticles using the bark extract of Pterocarpus marsupium and to evaluate its biomedical applications. Methods: Various concentrations of zinc acetate are used, and synthesis conditions were optimized to get a stable nanoparticle. The finest synthesis condition for zinc oxide nanoparticle production was at pH 7 with 20 ml extract, zinc acetate 10 mM, and 120 min of reaction time. The synthesized nanopowder was characterized using various analytical techniques, such as ultraviolet (UV)-visible spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The synthesized nanoparticles were tested for their antimicrobial, anti-inflammatory, inhibition of lipid peroxidation, and inhibition of amylase activity. Results: The size range of nanoparticles obtained was in the range of 10–32 nm as reported by SEM. The UV-visible absorption spectrum of the synthesized nanoparticle showed a peak at 340 nm, which confirmed the presence of nanoparticles. FTIR spectroscopy analysis indicated the presence of zinc oxide stretching at 666.22 cm-1. Further, the IR spectra indicated the presence of alcohols and acids, which can act as capping agents around the nanoparticles. XRD analysis confirmed the crystalline nature of nanoparticles. The synthesized nanoparticle showed appreciable antimicrobial activity. Zinc oxide nanoparticles at 40 μg/well were tested against phytopathogens, Pseudomonas aeruginosa, Staphylococcus aureus, Aspergillus flavus, and Aspergillus niger showed 16, 13, 15, and 16 mm zones of inhibition, respectively. The synthesized nanoparticle showed a considerable increase in inhibition of lipid peroxidation and amylase activity. The nanoparticle also exhibited appreciable anti-inflammatory activity measured by the inhibition of albumin denaturation. Conclusion: The study instigates the simple and convenient method of synthesizing zinc oxide nanoparticles using P. marsupium and its few biomedical applications.